Phthalate mixtures in pregnancy, autistic traits, and adverse childhood behavioral outcomes. (February 2021) - Day, Drew B.; Collett, Brent R.; Barrett, Emily S.; Bush, Nicole R.; Swan, Shanna H.; Nguyen, Ruby H.N.; Szpiro, Adam A.; Sathyanarayana, Sheela
Highlights: Maternal gestational phthalate mixtures were associated with child behavior. Early pregnancy phthalates were associated with autistic traits in both sexes. Early pregnancy phthalates were associated with worse adaptive skills in girls. Late pregnancy phthalates were associated with higher externalizing behavior in boys. MBzP and MCPP were important phthalates in almost all mixture associations. Abstract: Background: Prenatal exposure to multiple phthalates is ubiquitous, and yet few studies have evaluated these exposures as a mixture in relation to child autistic traits and behavioral problems. Objectives: To assess cumulative associations between prenatal phthalate mixtures and child behaviors, including effect modification by exposure timing and child sex. Methods: Analyses included 501 mother/child pairs from the multicenter pregnancy cohort The Infant Development and Environment Study (TIDES). Nine maternal urinary phthalate metabolites were measured in early and late pregnancy, and behavior was assessed at ages 4–5 years using composite T scores for the Behavioral Assessment System for Children (BASC-2), which measures several dimensions of child behavior, and the Social Responsiveness Scale (SRS-2), which measures social impairment consistent with autistic traits. We utilized weighted quantile sum (WQS) regressions to examine pregnancy period-specific associations between phthalate mixtures and behavioral outcomes. Full-sample 95% WQS confidence intervals are known to be anti-conservative, so we calculated a confirmatory p-value using a permutation test. Effect modification by sex was examined with stratified analyses. Results: A one-quintile increase in the early pregnancy phthalate mixture was associated with increased SRS-2 total score (coefficient = 1.0, confirmatory p = 0.01) and worse adaptive skills (coefficient = −1.0, confirmatory p = 0.06) in both sexes. In sex-stratified analyses, the early pregnancy phthalate mixture was associated with increased SRS-2 total score in boys (coefficient = 1.2, confirmatory p = 0.04) and girls (coefficient = 1.0, confirmatory p = 0.10) and worse BASC-2 adaptive skills score in girls (coefficient = −1.5, confirmatory p = 0.06), while the late pregnancy phthalate mixture was associated with increased BASC-2 externalizing score in boys (coefficient = 1.3, confirmatory p = 0.03). Conclusion: Our results suggest cumulative adverse associations between prenatal phthalate mixtures and multiple facets of childhood behavior.